Integral approach for the evaluation of poultry manure, compost, and digestate: Amendment characterization, mineralization, and effects on soil and intensive crops - Rizzo, Pedro Federico; Young, Brian Jonathan; Pin Viso, Natalia Daniela; Carbajal, Jazmin; Martínez, Laura Elizabeth; Riera, Nicolas Iván; Bres, Patricia Alina; Beily, María Eugenia; Barbaro, Lorena Alejandra; Farber, Marisa Diana; Zubillaga, Marta Susana; Crespo, Diana Elvira (Elsevier, 2022)
The egg industry has increased its production worldwide during the last decades. Several waste management strategies have been proposed to treat large volumes of poultry manure. Composting and anaerobic digestion are the main stabilization processes used. However, there are disagreements on the criteria for applying raw and treated poultry manure to the soil. We studied the relationship between physicochemical, toxicological, microbiological, parasitological, and metabarcoding parameters of raw and treated poultry manure (compost and digestate). Subsequently, we evaluated the mineralization of C, N and P, and the effects of amended soil on horticultural and ornamental crops. Compost and digestate presented better general conditions than poultry manure for use as organic soil amendments. The highest pathogenic microorganism content (total and fecal coliforms, Escherichia coli, and Salmonella spp.) was recorded for poultry manure. Multivariate analyses allowed associating a lower phytotoxicity with compost and a higher microbial diversity with digestate. Therefore, only compost presented stability and maturity conditions. We found high released CO2-C, N loss, and P accumulation in soil amended with a high dose of poultry manure during mineralization. However, high doses of poultry manure and digestate increased the biomass production in the valorization assay. We recommend the soil application of stabilized and mature poultry manure-derived amendments, which reduce the negative impacts on the environment and promote more sustainable practices in agricultural systems.